SOIL MANAGEMENT AND NITROGEN IN PRODUCTIVITY OF UPLAND RICE - BONINI, Carolina dos Santos Batista; ALVES, Marlene Cristina; NASCIMENTO, Vagner do; ARF, Orivaldo; COSTA, Nídia Raquel (Revista Brasileira de Engenharia de Biossistemas, 2010)
In loamy soils, in the irrigated areas and cultivated with no-till the problem of the compact subsuperficial associated to the concerns with the appropriate handling of the nitrogen manuring, they are challenges that need solutions. It gave way, intended the study with the objective of evaluating the behavior of the rice of high lands in no-till under the effects of different types of breaking of the soil and doses of N. The used experimental delineate was of blocks casualizados with 12 constituted by the combination of two mechanisms of breaking of the soil (I dial double and chisel plow) and doses of nitrogen (0, 25, 50, 75, 100 and 125 kg ha-1) in covering in the system of no-till, with four repetition. They were appraised: panicles number. m-2, number of spigots grenades and doddering, mass of 100 grains, productivity of grains. In agreement with the obtained results it can be concluded that there was influences positive in the different mechanisms and doses of used N. The increase in N rates on coverage provided, on average, an increase of 11.0% in rice productivity, the rate of 75 kg ha-1 compared with the control without N.